Lower extremity kinematics of ski motion on hills - Park, S. K.; Yoon, S.; Ryu, J.; Kim, J.; Kim, J. M.; Yoo, S. H.; Jeon, H. M.; Ha, S.; Cho, H. J.; Park, H. R.; Park, S. H.; Lim, G. Y.; et al. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
This research study aimed to collect thre- dimensional joint angles of the lower extremity during a basic ski motion in order to provide more quantitative teaching guide-lines for ski instructors. Eleven infrared cameras were placed to cover the capture volume of three different stopping movements (e.g. "Pflug Fahren") on hills. Six ski instructors participated in the test. Three trials of each stop were selected for comparison. Based on the results, skiers tended to use the edge of the ski and maintain a wider "V" shape at the shortest stop distance (e.g. 2m) compared to the other stops. Also, each skier had to invert the foot with a less flexed and more abducted knee and hip position as the stopping distance was decreased. This information will be useful for the development of more objective teaching guide-lines for beginner skiers.